Fuzzy Logic Based Secured Routing In Vanets - et. al., J. Stalin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vehicular Adhoc Network (VANET) is becoming a fundamental important component of Intelligent Transport System (ITS). VANET is one of the evolutionary network for providing safety related services, management of traffic and other user related services. VANET communication involves either Vehicle to Infrastructure (V2I) or Vehicle to Vehicle (V2V). In the current scenario, Multi-hop Authenticated Proxy Mobile IP (MA-PMIP) scheme is used in VANET where only 3G networks is considered and the scheme is unable to support transmission of substantial massive data while maintaining the security. The performance of MAPMIP drastically degrades during transmission of huge volume of data which leads to huge power dissipation. To overcome these problems a novel Fuzzy logic Based Secured Routing (FBSR) mechanism is proposed. The FBSR prevents Sink hole attack and Sybil attack. In order to avoid collision during large file transfer, TDMA and multi-threading concepts are introduced in FBSR. Furthermore, the performance of FBSR is compared with contemporary routing protocols OLSR and AODV.